2011
DOI: 10.1021/pr200473a
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Proteins Differential Expression during Honeybee (Apis mellifera L.) Queen and Worker Larvae Caste Determination

Abstract: Despite their similar genetic makeup, honeybee (A. mellifera) queens and workers show alternative morphologies driven by nutritional difference during the larval stage. Although much research have been done to investigate the causes of honeybee caste polymorphism, information at subcellular protein levels is limited. We analyzed queen- and worker-destined larvae mitochondrial proteome at three early developmental stages using combinations of differential centrifugation, two-dimensional electrophoresis, mass sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 63 publications
1
13
1
Order By: Relevance
“…This is in contrast to studies done in A. mellifera that suggest an increase in energy generation in queen-destined larvae ( Corona et al 1999 ; Li et al 2010 ; Begna et al 2011 ; Cameron et al 2013 ). However, in honeybees, growth rates of queen-destined larvae predominantly increase late in development and queens develop faster than workers ( Page and Peng 2001 ).…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…This is in contrast to studies done in A. mellifera that suggest an increase in energy generation in queen-destined larvae ( Corona et al 1999 ; Li et al 2010 ; Begna et al 2011 ; Cameron et al 2013 ). However, in honeybees, growth rates of queen-destined larvae predominantly increase late in development and queens develop faster than workers ( Page and Peng 2001 ).…”
Section: Discussioncontrasting
confidence: 88%
“…Components of this secretion, including Royalactin, Major Royal Jelly proteins, and a fatty acid Histone Deacetylase inhibitor, likely activate epidermal growth factor receptor (EGFR) signaling in the larval fat body ( Kamakura 2011 ), which in turn activates downstream pathways that directly or indirectly affect developmental trajectories (e.g., insulin-like signaling, PI3K/TOR/S6K, Ras/Raf/MAPK; Patel et al 2007 ; Kamakura 2011 ; Mutti et al 2011 ; Wolschin et al 2011 ; Badisco et al 2013 ). Experimental gene knock-downs, as well as comparative transcriptome and methylome studies, performed mostly in honeybees, have revealed extensive caste-dependent changes in gene expression and epigenetic regulation ( Kucharski et al 2008 ; Elango et al 2009 ; Bonasio et al 2012 ; Shi et al 2012 ; Simola, Ye, et al 2013 ) for a wide range of genes, for example, hexamerins ( Hoffman and Goodisman 2007 ; Hunt et al 2007 ; Cameron et al 2013 ), cytochrome P450s, spliceosomal genes ( Cameron et al 2013 ), the hypoxia pathway ( Azevedo et al 2011 ), and several other metabolic and developmental genes ( Evans and Wheeler 2001 ; Barchuk et al 2007 ; Hoffman and Goodisman 2007 ; Li et al 2010 ; Begna et al 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…The sampling times were at 3, 4, and 5 days post hatching from eggs (5 queens and 10 workers/day). The detailed sampling method is referred to the reports of Li et al (2010) and Begna et al (2011 , 2012) . DNA was Isolated using the Universal Genomic DNA Extraction Kit (TaKaRa, DV811A).…”
Section: Methodsmentioning
confidence: 99%
“…The identification of protein spots was carried out as described by Begna et al with some modifications [ 22 ]. Interesting protein spots from the preparative gels were in-gel digested and identified by LC-Chip ESI-QTOF-MS (Q-TOF 6520, Agilent, Santa Clara, CA).…”
Section: Methodsmentioning
confidence: 99%